Importance of future motivation for skill acquisition among medical students undergoing endoscopic forceps training - Go Kamimura; Koki Maeda; Masaya Aoki; Satomi Imamura; Shoichiro Morizono; Takuya Tokunaga; Tadashi Umehara; Aya Harada-Takeda; Toshiyuki Nagata; Kazuhiro Ueda (BMC Medical Education)
Abstract Background In recent years, surgical procedures have shifted from open thoracotomy and laparotomy to minimally invasive endoscopic surgery, making endoscopic forceps training essential. In our department, we teach endoscopic forceps training to medical students in dry laboratories. We examined differences in the skill acquisition of medical students undergoing endoscopic forceps training. Methods Ninety-eight fourth-grade students at Kagoshima University Graduate School of Medicine underwent endoscopic forceps training every day in a dry laboratory during a two-week period in our department. Before the start of the training, we administered a questionnaire. We focused on the differences in skill acquisition levels between the first and second halves of the training period. Results Twenty-eight of the 63 male students and 9 of the 35 female students aspired to become surgeons (hereafter: “aspiring surgeon group”). All students showed a significant improvement in their skill acquisition from the first to the second half (p < 0.001). At the start of training, there was no difference in skill acquisition between the 37 in the aspiring surgeon group and the other students. However, during the second half of the training, the aspiring surgeons acquired skills significantly faster (p = 0.007). Among them, male aspiring surgeons, in particular, acquired skills significantly faster. Focusing on the speed of skill acquisition, there was no correlation between sex (p = 0.18) or sports activity (p = 0.64) and improvement in endoscopic forceps skills. Conclusions In dry laboratory endoscopic forceps training among medical students, all participants showed skill improvement with repeated practice. However, aspiring surgeons demonstrated significantly faster improvement, likely due to clear goal setting. As demonstrated in this study, goal-setting in student education may be associated with skill acquisition.